Critical Success Factors for the Development and Sustainability of Smart Tourism in Laos, A Case study of Oudomxay Province - ONOMAKE , Efe; MANYPHONE, Kongy (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The purpose of this research is to identify the critical factors necessary for the development and implementation of smart tourism in Laos. Smart tourism which has been the new trend in tourism over the last decade was born out of the application of modern technological devices for accessing tourist attractions, information, sites, and other hospitality services due to the increased use and proliferation of digital devices, laptops, computers and increased connectivity around the world. However, smart tourism has unfortunately not been sufficiently exploited in Laos. As Laos cannot yet boost of any smart tourist destinations due to the lack of development of the appropriate technological and logistical infrastructure to support smart tourism. As a result, Laos is not yet ripping from the many economic benefits of smart tourism which are very enormous. The research has been able to identify the influential success factors necessary for Oudomxay a notable eco-tourism location to be upgraded to a smart tourist destination. The research made use of a quantitative and qualitative method of a SWOT analysis combined with the AHP Model. We were able to determine the critical strategic factors necessary for transforming Oudomxay into a smart tourist destination by combining SWOT with AHP techniques. We enhanced the SWOT analysis with a multicriteria decision-making technique called the Analytic Hierarchy Process (AHP). AHP approach achieves pairwise comparisons among factors or criteria in order to prioritize them using the eigenvalue calculation. The aim of applying the combined method is to improve the quantitative side of strategic planning. Calculated priorities of SWOT factors could Good Number of Eco and Nature tourist attractions is the most important factor to be considered with an overall priority value of ( 0.197) for strength. For Opportunities, Government intervention plan to upgrade to Smart City carries the highest points. (0.185), while for weakness. Lack of Digitalized Public Transportation (0.124) is the highest and for threats, Increased cost of living or inflation. (0.086) The Conceptual model elucidated and highlighted the critical success factors for the successful implementation of smart tourism in Oudomxay. The results obtained can be used to develop a detailed management approach for critical decision making or to develop a set of appropriate alternatives strategy for the development, implementation, and sustainability of smart tourism in Oudomxay. This Research aims to increase the competitive advantage of Oudomxay to be a unique and exotic tourist destination and to update the Ideas of previous research works on the tourism industry of Laos.